A community-focused rural academic health department model in North Carolina: elevating community engagement, rural public health practice and research - Carmen D. Samuel-Hodge; Lisa Macon Harrison; Wendy Smith; Karl T. Johnson; Anna Feng; Devon Noonan (Frontiers in Public Health, 2026)
Introduction In decentralized public health systems, rural public health departments have fewer economic resources and higher needs for public health programs and services. This case study describes the evolution of a rural district health department’s community and academic partnerships across three phases. Throughout this process, partnerships grounded in community engagement informed the local public health workforce, translated research into practice, and supported the design, implementation, and evaluation of interventions in a rural setting. Methods Our approach is guided by three established models—a logic model for evaluating academic health departments (AHD), staged process model of AHD development, and a model of organizational change strategies. Results Over a decade of building a rural AHD has resulted in more than $22 million in grant funding, an increase in implemented evidence-based interventions, improved workforce capacity, and expanded formal collaborations with faculty at academic institutions. Discussion A mutually shared value of community health improvement and support with a consistent focus on community voice and community health priorities are the threads of success for this rural academic health department model in north-central North Carolina.